Enterococcus faescium filtrate suppresses Salmonella Heidelberg in broilers - Fernanda Barthelson Carvalho de Moura; Gabriella Costa Ribeiro; John Kastelic; Alessandra Melchert; Taís Gomes Colleti; Ana Carolina Izidoro de Moraes; Gabriele Silva Dias; Guilherme de Brito Viana; Raphael Lucio Andreatti Filho; Adriano Sakai Okamoto (Ciência Rural)
ABSTRACT: The objective was to investigate the ability of a filtrate produced by the lactic acid bacterium Enterococcus sp. to control Salmonella Heidelberg in vivo. We determined that Enterococcus sp. had an antagonistic effect on Salmonella Heidelberg, based on in vitro testing (spot-on-the-lawn method). For in vivo studies, broiler chickens (n = 32), 15 d old, were allocated into 4 groups. Filtrate was given prophylactically once daily orally at 15-19 d of age to 8 birds, followed by an S. Heidelberg challenge to 16 birds at 20 d; 5 of 8 and 3 of 8 birds in treated and control groups, respectively (P = 0.32), had < 10 CFU/g of S. Heidelberg in their cecum at 21 d. In a therapeutic study with 16 birds challenged with S. Heidelberg at 15 d, we gave to 8 birds oral therapeutic filtrate once a day at 16 to 20 d had 5250 cfu/g of the pathogen in the cecum versus 912,950 cfu/g in the control, a 174-fold reduction. We concluded that filtrate has potential as a non-antibiotic approach to control S. Heidelberg in vivo.